PERAN KEBERFUNGSIAN KELUARGA TERHADAP PENERIMAAN DIRI REMAJA - Haiyun Nisa; Muharrami Yulia Sari (State Islamic University (UIN) Ar-Raniry, 2019)
SOS Children's Villages is one of foster care that has family care concept. Self-acceptance can be built through the functioning of the family. One of the success factors of adolescents who stay in foster care is the extent of adolescence can accept his/her condition. This study purpose to investigate empirically the relationship between the foster family functioning and self-acceptance of adolescence in SOS Children's Villages Banda Aceh. The sampling technique used in this research is purposive sampling. These samples included 31 adolescence consisting were male whose age ranged between 15-17 years and female 15-21 years who live in SOS Children's Villages Banda Aceh. The following instruments were used are Family Assessment Device by Ryan et al., and Self-Acceptance Scale which constructed based on Berger theory. The results of data analysis using Pearson correlation technique showed a correlation coefficient (r) of 0.456 and p = 0.010 (p <0.05). It means there is a positive correlation between family functioning and self-acceptance of adolescence in SOS Children's Villages Banda Aceh. The more effective of family functioning, the higher level of self acceptance or otherwise.